Translators Producing Knowledge: Where There Is No Doctor in Tamil - LILLIAN WALKOVER (Engaging Science, Technology, and Society, 2019)
Where There Is No Doctor is one of the most widely used community health books in the world and has been translated into over 80 languages. This paper traces four aspects of translation in Tamil-language editions of the text, including Doctor Illaadha Idaththil and related books. First, translators choose and create language to produce a colloquial text related to, but different from, the original. Second, the translated text, as part of a genre of health writing, is edited to motivate readers to take new and different actions related to their bodies and wellbeing. Third, the success of this work is assessed by asking future readers to respond to the draft. Finally, the finished translation circulates to new arenas, influencing popular writing on health and ways of understanding the body. Analyzing the translation of a health text through the lens of postcolonial translation studies, this paper argues that the translation and adaptation of Where There Is No Doctor and the books it inspired engage translators, clinicians, and future readers in a transnational knowledge production process.